Strategi Penyerapan Anggaran yang Partisipatif dan Kolaboratif dalam Mendorong Pertumbuhan Ekonomi pada Pemerintah Daerah Kabupaten Lombok Tengah - Fathurrahman, Fathurrahman (Nakhoda: Jurnal Ilmu Pemerintahan, 2023)
This study discusses the constraints in budget utilization and formulates a participatory and collaborative strategy in encouraging economic growth in the Central Lombok Regency Regional Government. This study is intended to analyze the constraints faced so as to formulate strategies using the SOAR method. The type of research used in this study is descriptive qualitative using observation, interview and FGD methods. In formulating the Strategy, this study used SOAR analysis. The study results reveal that there are several obstacles in budget absorption in Central Lombok Regency including: (1) Low technical and managerial skills of local government apparatus in managing the budget; (2) limited adequate facilities and infrastructure to implement development projects; (3) the existence of complex and slow bureaucratic problems in the process of procuring goods and services; (4) lack of coordination and communication between work units within the local government which hinders the effectiveness of budget absorption; (5) lack of public awareness and participation in monitoring the use of local budgets. Meanwhile, to overcome these obstacles, several strategies have been formulated by analyzing them using SOAR. The results of the analysis resulted in several strategies including: Some strategies that have been formulated by looking at strengths and appreciation include: (1) Increasing human resource capacity such as training for PPK, treasurer, finance manager and goods and services manager; (2) Preparing measurable financial planning such as each activity must have a measurable indicator target; (3) Simplifying the process of procuring goods and services. In addition, strategies that have been formulated by looking at opportunities and appreciation include (1) Creating cooperation between actors in the budget absorption process; (2) Strong commitment from the leadership; (3) Creating effective communication in work activities. When looking at the strategies generated by looking at strengths and results, several strategies are obtained, among others: (1) Maximizing the potential of existing human resources so that budget absorption is on time; (2) Ensuring that the budget is used effectively and efficiently. For the next stage, see the strategies resulting from identifying opportunities and results including: (1) Expanding the network of cooperation so that the budget allotted can be maximized properly; (2) Arranging measurable programs and activities so that there is no accumulation of work at the end of the year.